Russian Conflict On Ukraine Based On Humanitarian Law Perspective - Yuanda Winaldi; Joko Setiyono (LAW REFORM, 2022)
Russia's conflict with Ukraine which has lasted for a long time has resulted in world commotion and disorder. This problem is certainly an important legal issue to be researched. Based on this, this study aims to examine and analyze the humanitarian law arrangements against Russia's armed attack on Ukraine. The research conducted in this paper is a type of doctrinal research. The conclusion is that based on international humanitarian law arrangements such as the Geneva Conventions, Additional Protocol I 1997 provides protection for civilians and civilian objects in times of war. Russia's act of armed attack is a violation of international humanitarian law. It is hoped that proactive actions from the United Nations will be neutral by carrying out a peaceful settlement. However, if it fails to produce a decision that resolves the conflict, strict sanctions are needed against the violator in accordance with the applicable international humanitarian law regulations.